Microalgal proteins as ingredients for creating dairy mimetic products: Prospects for substituting bovine milk proteins - Jayani Samarathunga; Thi Phuong Linh Le; Max Gabard; Katrina Strazdins; Jeroen Rens; Benu Adhikari (Future Foods)
Growing concerns about the sustainability of food supply and animal welfare have fueled increased interest in dairy mimetic products. These alternatives largely meet the nutritional and caloric needs of consumers who avoid animal-based foods or follow a flexitarian diet. Due to their balanced amino acid profile, high digestibility, and superior techno-functional properties, microalgal proteins are emerging as promising ingredients, often outperforming terrestrial plant proteins in several respects. Notably, calcium-chelating peptides from microalgae offer osteogenic benefits, highlighting a key health advantage. While the incorporation of microalgal biomass in dairy products has been studied, the protein-mimicking potential of microalgal proteins remains underexplored. This review provides a comprehensive overview of the types and nature of dairy mimetic products, with an emphasis on the role of microalgal biomass and proteins in replicating the functional properties of dairy proteins. Evidence suggests that microalgal proteins more closely mimic bovine milk proteins than whole microalgal biomass. Additionally, key physicochemical properties necessary for the successful application of microalgal proteins in dairy and dairy-mimetic products, such as yogurt, cheese, emulsions, and gels, are discussed.